Design and Build Applications for Maternal and Child Health Promotion and Services to Overcome Stunting in NTT Province - Eltyasar Putrajati Noman; Made Kamisutara (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2022)
A good level of health enables everyone to live socially and economically productive lives. The government has determined the acceleration of stunting reduction as the main project because the proportion of stunted children under five is a very important parameter for the development of human and national capital. Based on data, the Province of East Nusa Tenggara (NTT) is the area with the highest prevalence of stunting in Indonesia but the second lowest Information Technology Development Index in Indonesia. Therefore, the purpose of this research is to design and build applications for promotion and services for maternal and child health to overcome stunting in the province of NTT, so that improving the quality of health promotions and services, can have an impact on changes in public health services. The design and development of this application use a spiral model so that the application can later be adopted for use within the scope of the NTT Province and continue to be improved and developed in the future. This application is built using Code Igniter 4 framework and MySQL database. In this web-based application for promotion and maternal and child health services, it will be easier for people in NTT Province to get information about immunization schedules, location of health facilities, learning articles, and local government publications related to maternal and child health within the scope of NTT Province. This application is built using Code Igniter 4 framework and MySQL database. In this web-based application for promotion and maternal and child health services, it will be easier for people in NTT Province to get information about immunization schedules, location of health facilities, learning articles, and local government publications related to maternal and child health within the scope of NTT Province. This application is built using Code Igniter 4 framework and MySQL database. In this web-based application for promotion and maternal and child health services, it will be easier for people in NTT Province to get information about immunization schedules, location of health facilities, learning articles, and local government publications related to maternal and child health within the scope of NTT Province.